Digital Distribution Channels as Catalysts for Sustainable Local Tourism: Examining Tourist Behavioral Intentions in Vietnam - Hoang, Vu Hiep; Ngo, Quoc Dung; HA, Khanh Linh (Journal of Posthumanism, 2025)
This study examines the transformative role of digital distribution channels in fostering sustainable local tourism through an investigation of tourist behavioural intentions within the Vietnamese context. Employing a quantitative methodology integrating structural equation modelling (SEM) with fuzzy-set qualitative comparative analysis (fsQCA), the research develops a comprehensive theoretical framework that synthesises technology acceptance theory, planned behaviour theory, and sustainability paradigms. Data collection encompassed 487 respondents through a stratified sampling approach across Vietnam’s key tourist destinations. The measurement model demonstrated robust reliability and validity through exploratory and confirmatory factor analyses, whilst the structural model revealed significant positive relationships between digital channel attributes, perceived sustainability value, and tourist behavioural intentions. The fsQCA findings complemented the SEM results by identifying configurational pathways to high behavioural intentions, revealing that traditional demographic factors interact complexly with digital engagement patterns. The study contributes theoretically by proposing a novel Digital-Sustainability Tourism Acceptance Model and methodologically by demonstrating the complementary insights gained from combining variance-based and set-theoretic approaches. Practically, the findings provide strategic guidance for destination management organisations and tourism enterprises seeking to leverage digital technologies for sustainable tourism development. The research establishes that digital distribution channels function not merely as booking platforms but as catalysts for sustainable tourism practices, fundamentally reshaping tourist-destination relationships in emerging economies.